2006
DOI: 10.1016/j.energy.2005.11.007
|View full text |Cite
|
Sign up to set email alerts
|

After-hours power status of office equipment in the USA

Abstract: Office equipment is expected to be the fastest-growing segment of commercial energy use over the next 20 years, yet many aspects of office equipment energy use are poorly understood. User behavior, such as turning off devices at night or enabling power management, influences energy use to a great extent. The computing environment also plays a role both in influencing user behavior and in the success of power management. Information about turn-off rates and power management rates for office equipment was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 6 publications
(20 reference statements)
4
74
0
1
Order By: Relevance
“…These energy-savings mechanisms can be accessed by the operating system via the Advanced Configuration and Power Interface, and the operating system's power management tools permit users to select trade-offs between machine characteristics and battery life (Microsoft 2009). However, most users do not take advantage of the power management features on their PCs (Webber et al 2005). Further, as the design focus is on extending battery life, not on minimizing overall energy consumption, the laptop typically operates in a high-energy mode while on AC power, thereby forgoing the energysavings opportunities offered by the laptop.…”
Section: Power Management Technologiesmentioning
confidence: 99%
“…These energy-savings mechanisms can be accessed by the operating system via the Advanced Configuration and Power Interface, and the operating system's power management tools permit users to select trade-offs between machine characteristics and battery life (Microsoft 2009). However, most users do not take advantage of the power management features on their PCs (Webber et al 2005). Further, as the design focus is on extending battery life, not on minimizing overall energy consumption, the laptop typically operates in a high-energy mode while on AC power, thereby forgoing the energysavings opportunities offered by the laptop.…”
Section: Power Management Technologiesmentioning
confidence: 99%
“…Webber et al [16] also collected data on devices, focusing on the after-hours power state of networked devices in office buildings: they showed that most of devices are left powered on during night, concluding that this is the first cause of energy waste.…”
Section: Related Workmentioning
confidence: 99%
“…Occupant actions can also lead to excessive and unnecessary energy consumption [28]. In the United States' commercial built environment, less than half of most buildings' appliances and systems are turned off by occupants after operational hours [29]. Due to the fact that there are more non-working hours in a week than working hours, such behaviors can lead to more energy wasted during non-working hours than energy used during working hours [30].…”
Section: Introductionmentioning
confidence: 99%